Challenging the Negative Perception of Lithium and Optimizing Its Long-Term Administration - Rybakowski, Janusz K. (Frontiers in Molecular Neuroscience, 2018)
The use of lithium for the prevention of recurrences in mood disorders has a 55-year history. Nowadays, lithium is universally accepted as the first choice mood-stabilizer for maintenance treatment of bipolar disorder. In addition to its mood-stabilizing properties, lithium exerts anti-suicidal, immunomodulatory and neuroprotective action which may further substantiate its clinical usefulness. Despite these facts, the use of lithium in mood disorders has been greatly underutilized. The reasons include the introduction and promoting other mood stabilizers as well as a perception of lithium as a “toxic drug” due to its side effects, mainly thyroid, renal and cognitive disturbances. The trends in lithium prescription in recent decades show relative stability or a decline at the expense of other mood-stabilizing drugs, both first generation (valproate) and second generation (olanzapine, quetiapine, lamotrigine). In this paper, the negative perception of lithium by some clinicians will be challenged. First, the data showing lithium superiority over other mood stabilizers will be presented. Secondly, the lithium-induced side effects which can make a hindrance for a more frequent application of this drug will be delineated, and their proper management described. Finally, an issue of benefits of long-term administration of lithium will be discussed, including the phenomenon of the “excellent lithium responders” as well as a subject of starting lithium prophylaxis early in the course of the illness. This review is based on the 47-year experience with lithium therapy by the author of the article.